Network pharmacology and experimental validation to explore the potential mechanism of Sanjie Zhentong Capsule in endometriosis treatment - Guo, Ruoyi; Yi, Zhihui; Wang, Yun; Wang, Li (Frontiers in Endocrinology, 2023)
Purpose: Sanjie Zhentong Capsule (SZC) is gradually becoming widely used in the treatment of endometriosis (EMs) and has demonstrated an excellent curative effect in the clinic. However, the active components and mechanisms of Sanjie Zhentong Capsule (SZC) in the treatment of endometriosis (EMs) remain unclear, and further research is needed to explore the effects of Sanjie Zhentong Capsule (SZC). Materials and methods: First, a drug target database of Sanjie Zhentong capsule (SZC) was established by consulting the TCMSP database and related literature. An endometriosis (EMs) disease target database was then established by consulting the GeneCards, OMIM and Drug Bank databases. The overlapping genes of SZC and EMs were determined, and protein-protein interactions (PPIs), gene ontology (GO) and Kyoto Gene and Genome Encyclopedia (KEGG) analyses were performed to predict the potential therapeutic mechanisms. Molecular docking was used to observe whether the key active ingredients and targets predicted by network pharmacology had good binding energy. Finally, in vitro experiments such as CCK-8, flow cytometry and RT-PCR assays were carried out to preliminarily verify the potential mechanisms. Results: Through the construction of a pharmacological network, we identified a total of 28 active components in SZC and 52 potential therapeutic targets. According to GO and KEGG enrichment analyses, the effects of SZC treatment may be related to oxidative stress, steroid metabolism, apoptosis and proliferation. We also experimentally confirmed that SZC can regulate the expression of steroid hormone biosynthesis-related genes, inhibit ectopic endometrial stromal cell (EESC) proliferation and oxidative stress, and promote apoptosis. Conclusion: This study explored the potential mechanism of SZC in the treatment of EMs through network pharmacology and experiments, providing a basis for further future research on SZC in the treatment of EMs.